2016
DOI: 10.3109/10408363.2015.1136259
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione in metastases: From mechanisms to clinical applications

Abstract: Metastatic spread, not primary tumors, is the leading cause of cancer death. Glutathione (γ-glutamyl-cysteinyl-glycine, GSH) is particularly relevant in cancer cells as it is involved in regulating carcinogenic mechanisms, growth and dissemination, and multidrug and radiation resistance. Upon interaction of metastatic cells with the vascular endothelium, a high percentage of metastatic cells with high GSH levels survive the combined nitrosative and oxidative stresses elicited by the vascular endothelium. GSH r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 184 publications
0
30
0
Order By: Relevance
“…Despite the MR-induced reduction in hepatic GSH, MR does not increase oxidative stress, in part because MR enhances antioxidant capacity and increases proton leak in the liver, likely decreasing ROS production [51]. The ability of MR to increase GSH levels in red blood cells is significant because of the role of GSH in the neutralization of ROS [52]. Several animal studies have shown restricting dietary methionine by just 40% reduces mitochondrial ROS production in several tissues, resulting in reduced mitochondrial DNA oxidative damage in vivo [30,53,54].…”
Section: Glutathione Formationmentioning
confidence: 99%
“…Despite the MR-induced reduction in hepatic GSH, MR does not increase oxidative stress, in part because MR enhances antioxidant capacity and increases proton leak in the liver, likely decreasing ROS production [51]. The ability of MR to increase GSH levels in red blood cells is significant because of the role of GSH in the neutralization of ROS [52]. Several animal studies have shown restricting dietary methionine by just 40% reduces mitochondrial ROS production in several tissues, resulting in reduced mitochondrial DNA oxidative damage in vivo [30,53,54].…”
Section: Glutathione Formationmentioning
confidence: 99%
“…Our results show that both BSA‐AuNCs and AuNCs@PAH do not affect cell viability at concentrations up to 0.6 mg mL −1 ( Figure a). It was reported recently that a high percentage of metastatic cells with high GSH levels survived under the combined nitrosative and oxidative stresses elicited by the vascular endothelium, and GSH level in lung tumors ranged from 0.5 to 3 m m , while GSH level in normal lung tissue was four times lower . Hence the difference in GSH concentration in healthy and tumorigenic tissues could be used to image the location of tumors by detecting the change of PL intensity of AuNCs.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid the detrimental effects of ROS, cancer cells actively upregulate multiple antioxidant systems [58,80,83,84]. As a result, many cancer cells contain high GSH concentrations and overexpress the related enzymes, such as GGT [20] and GST [64,85]; high GSH concentrations are generally beneficial to initiation, progression, and metastasis of cancers [13,78,79,84,86,87]. Multidrug and radiation resistance of many tumors appears to be associated with higher GSH levels and/or lower ROS levels in the cancer cells [13,58,86,88].…”
Section: Expert Opinionmentioning
confidence: 99%
“…As a result, many cancer cells contain high GSH concentrations and overexpress the related enzymes, such as GGT [20] and GST [64,85]; high GSH concentrations are generally beneficial to initiation, progression, and metastasis of cancers [13,78,79,84,86,87]. Multidrug and radiation resistance of many tumors appears to be associated with higher GSH levels and/or lower ROS levels in the cancer cells [13,58,86,88]. Consequently, it has been proposed that cancer patients should be treated with pro-oxidants that exacerbate oxidative stress or block metabolic adaptations that confer oxidative stress resistance [78,80,89].…”
Section: Expert Opinionmentioning
confidence: 99%